2011
DOI: 10.1523/jneurosci.4547-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variant of BDNF (Val66Met) Polymorphism Attenuates Stroke-Induced Angiogenic Responses by Enhancing Anti-Angiogenic Mediator CD36 Expression

Abstract: Brain-derived neurotrophic factor (BDNF) has been shown to be necessary and sufficient for post-stroke recovery in rodents. From these observations, we and others have hypothesized that a common single nucleotide polymorphism (SNP) in the pro-domain of bdnf that leads to a methionine (Met) substitution for valine (Val) at codon 66 (Val66Met) will affect stroke outcome. Here we investigate the effect of the BDNF genetic variant on ischemic outcome by using mice with a genetic knock-in of the human BDNF variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…Reduced BDNF signaling has been linked to altered differentiation of human fetal and adult oligodendrocyte progenitor cells (Cui et al, 2010) and to regional reductions of myelin-related proteins (Vondran et al, 2010), but these observations would be very difficult to relate to our associations with the Val allele of BDNF, which is the normal functional BNDF allele and has not been associated with reduced BDNF levels in human brain. The animal model literature is consistent in showing that the BDNF Met allele, which alters BDNF protein trafficking and secretion, is associated with reduced BDNF protein levels (Bath et al, 2012;Qin et al, 2011). In humans, the available post-mortem information involves only mRNA, which is not expected to be affected by the Val/Met polymorphisms (eg, http://braincloud.jhmi.edu/) and the results are consistent with this expectation (Colantuoni et al, 2011).…”
Section: Bdnf Val 66 Met Effects On Dti Measures In Normalsmentioning
confidence: 61%
“…Reduced BDNF signaling has been linked to altered differentiation of human fetal and adult oligodendrocyte progenitor cells (Cui et al, 2010) and to regional reductions of myelin-related proteins (Vondran et al, 2010), but these observations would be very difficult to relate to our associations with the Val allele of BDNF, which is the normal functional BNDF allele and has not been associated with reduced BDNF levels in human brain. The animal model literature is consistent in showing that the BDNF Met allele, which alters BDNF protein trafficking and secretion, is associated with reduced BDNF protein levels (Bath et al, 2012;Qin et al, 2011). In humans, the available post-mortem information involves only mRNA, which is not expected to be affected by the Val/Met polymorphisms (eg, http://braincloud.jhmi.edu/) and the results are consistent with this expectation (Colantuoni et al, 2011).…”
Section: Bdnf Val 66 Met Effects On Dti Measures In Normalsmentioning
confidence: 61%
“…This "neurovascular niche" contributes to functional recovery from stroke (Chopp et al, 2007;Ohab et al, 2006) and possibly to mitigating subtle cognitive deficits resulting from disease of the smaller vessels. Roles of BDNF in the dynamic interactions between neurogenesis (Guo et al, 2008;Louissaint et al, 2002) and angiogenesis (Qin et al, 2011) have been described, but remain to be fully characterized (Kim et al, 2004;Li et al, 2006). The clinical impact of BDNF signaling on cerebrovascular disease has been suggested by greater white matter hyperintensity volumes in carriers of the met BDNF allele 60 years of age or older (Taylor et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, with high affinity toward oxidized lipids and advanced glycation end products, CD36 has been implicated in the development of IR and diabetes (39)(40)(41). We previously reported increased CD36 mRNA levels in the brains of 9 month-old BDNF M/M mice (42). In this study, we observed that BDNF M/M mice fed a HFD develop extreme obesity even at younger ages (i.e., 14-weeks-old), which is accompanied with elevated expression of CD36 in the brain.…”
Section: M/mmentioning
confidence: 91%